2012
DOI: 10.4172/2155-9600.1000150
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Preparation of Fortified Sapota-Papaya Fruit Bar

Abstract: Food Enrichment and Fortification are the most cost effective and sustainable strategy to address the problem of micronutrient malnutrition. The study was conducted to standardize the protocol for preparation of sapota-papaya fruit bar and to enhance the nutritional value by fortifying with skim milk powder. For preparation of fruit bars, Sapota and Papaya pulp were blended in different proportions to standardize parameters like pectin, pulp combination and SMP concentration and the mixture was dried in mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…However, Hemakar et al (2000) evaluated a moisture content of 11.0 per cent in mango bars. Take et al (2012) also reported moisture content in the range of 14.64-15.91 per cent in fortified sapota-papaya fruit bar. The maximum moisture content in sweet and spiced aonla segments were observed in sucrose treatments, which may be attributed to almost twice the molecular weight of sucrose compared with glucose, which resulted in roughly half the molecular concentration of sucrose solution, and therefore lower osmotic pressure than the glucose solution and thus less water loss (Panagiotou et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Hemakar et al (2000) evaluated a moisture content of 11.0 per cent in mango bars. Take et al (2012) also reported moisture content in the range of 14.64-15.91 per cent in fortified sapota-papaya fruit bar. The maximum moisture content in sweet and spiced aonla segments were observed in sucrose treatments, which may be attributed to almost twice the molecular weight of sucrose compared with glucose, which resulted in roughly half the molecular concentration of sucrose solution, and therefore lower osmotic pressure than the glucose solution and thus less water loss (Panagiotou et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Similar trend was observed by Mir and Nath (2000) in mango bar enriched with desiccated coconut powder and soy protein concentrate and Shanthi (2000) in mango bar enriched with green gram. Increase in carotenoid content in fortified sapota -papaya fruit bar was reported by Take et al (2012).…”
Section: Resultsmentioning
confidence: 99%
“…There was an increase in carotenoids content as papaya pulp increased in blending ratio of fruit bar because papaya is a rich source of carotenoids [27]. The loss of carotenoids content in the processed samples was mainly due to non-oxidative changes (cis-trans isomerisation, epoxide formation of thermal degradation) or oxidative changes.…”
Section: Total Carotenoids (µG/100 G)mentioning
confidence: 99%